2017
DOI: 10.1021/acsami.6b15821
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of Membrane-Targeting Cationic Ligands on a Silver Nanoparticle Surface in an Antibiotic-Resistant Antibacterial and Antibiofilm Activity Assay

Abstract: To explore the structure-activity relationship of membrane-targeting cationic ligands on a silver nanoparticle surface in an antibiotic-resistant antibacterial and antibiofilm activity assay, a series of functionalized silver nanocomposites were synthesized. Tuning the structural configuration, molecular weight, and side-chain length of the cationic ligands on the nanoparticle surface provided silver nanocomposites with effective antibacterial activity against both antibiotic-resistant Gram-negative and Gram-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 51 publications
0
21
0
2
Order By: Relevance
“…Therefore, the important point is to determine the removal ability of NPs to mature MRSA biofilms. We executed XTT quantitative determination assay, 29 SEM test, and LIVE/ DEAD BacLightTM Bacterial Viability Kits staining experiment, 30 respectively. As shown in Figure 4a-1, at 0.1 μ mol/ mL, the removal effect of CA-BBR NPs on mature biofilms was 64.22 ± 3.0%, while the removal rate of BBR group was only 32.98 ± 1.62%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the important point is to determine the removal ability of NPs to mature MRSA biofilms. We executed XTT quantitative determination assay, 29 SEM test, and LIVE/ DEAD BacLightTM Bacterial Viability Kits staining experiment, 30 respectively. As shown in Figure 4a-1, at 0.1 μ mol/ mL, the removal effect of CA-BBR NPs on mature biofilms was 64.22 ± 3.0%, while the removal rate of BBR group was only 32.98 ± 1.62%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous reports showed that Ag nanocomposites (64 µg/mL) and cationic amphiphile could penetrate into the biofilms and eradicated them. Furthermore, AgNPs were reported to penetrate and disperse into biofilm matrixes and then deliver Ag + flux to the bacterial wall to eradicate the biofilms (Dai et al, 2017). Our results showed that Gram-positive bacteria were more resistant to AgPtNHs compared to Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 69%
“…In the biocide‐releasing approach, the biocidal agents are preloaded or embedded and slowly released into the vicinity environment to kill bacteria. The widely used biocidal agents in literature include silver nanoparticles (AgNPs), antibiotics, and nitrogen oxide (NO), etc. In particular, the AgNPs have been applied to polymeric surface coatings as a potent and broad‐spectrum antibacterial agent, and the released silver ions can bind to the bacterial membrane and inactivate the proteins, which cause the lysis of bacterial cells at the vicinity .…”
Section: Monofunctional Antibacterial Materialsmentioning
confidence: 99%